Development of nitrate ion-selective electrode sensor for precision agriculture / Norlaili Hanim binti Nordin - Nordin, Norlaili Hanim (2014)
Nitrate ion-selective sensors (ISE) was fabricated for the purpose of small, low cost, onthe-go and real-time nitrate ion monitoring for precision agriculture (PA) and the performance was evaluated. The sensor was constructed on two types of printed circuit board (PCB) which are PCB with and without silver (Ag) layer. Two different carbons i.e. Electrodag (ED) and Jujo (J) were printed on these PCB electrode surface. All these carbon boards were characterized using potentiostat. PCB without Ag layer which modified with ED followed by J carbon paste had shown current peak of 0.0055 mA. Conducting polymer polypyrrole (PPy) was deposited on each different types of electrodes and once again cyclic voltammetry shown that PCB without Ag layer which modified ED and J carbon give the highest anodic peak current i.e. 0.43 mA. The nitrate recognition sensor membrane was prepared by using tetraoctylammonium nitrate (TOAN) as ionophore with methyl methacrylate (MMA) and n-butyl acrylate (nBA) as plasticizer. The sensor performance was checked in different concentration of nitrate solution varied from 1 X 10-4 M to 1 X 10-1 M. PCB sensor tip without Ag layer with ED and J carbon pastes displayed slope value of -61.153 mV/decade, slightly exceed the Nernstian slope value for single ion detection which is -59.16 mV/decade. The linear range for the nitrate ISE is up to 1 X 10-5 M and limit of detection (LOD) is at 6.3 X 10-7 M of nitrate concentration. Temperature test was performed to study the nitrate ISE performance depreciation. It was found that at 10 ºC, the slope of the ISE sensor is around -50 mV/decade, which is below Nernstian response whereas sensor tip tested at 50 ºC shown super Nernstian behavior.